2015
DOI: 10.1111/pim.12217
|View full text |Cite
|
Sign up to set email alerts
|

Study of Toxocara seroprevalence among patients with allergy and healthy individuals in Bulgaria

Abstract: Data in the literature addressing the ability of Toxocara infection in humans to induce development of atopic disease are controversial. The aim of our study was to determine the seroprevalence of anti-Toxocara antibodies in three groups of people: subjects with allergic symptoms and presence of allergen-specific IgE, subjects with allergic symptoms and absence of allergen-specific IgE, and clinically healthy blood donors. Serum samples from all subjects were tested by ELISA and Western blot for presence of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Toxocariasis is a parasitic zoonotic disease with various clinical manifestations, protracted course, and common recurrences. In Bulgaria the exact incidence of human toxocariasis still not established, but significant information has been gathered over the last 10 years [24].…”
Section: Discussionmentioning
confidence: 99%
“…Toxocariasis is a parasitic zoonotic disease with various clinical manifestations, protracted course, and common recurrences. In Bulgaria the exact incidence of human toxocariasis still not established, but significant information has been gathered over the last 10 years [24].…”
Section: Discussionmentioning
confidence: 99%
“…Data published on toxocariasis show a widespread prevalence of this helminthosis, which is still a neglected and poorly evaluated problem (22). Our studies among healthy individuals in Bulgaria show 8.0% prevalence of Toxocariasis found in ELISA, and and 4.0% in WB (23). Studies on the prevalence of T. canis in animals in our country show that this is one of the most common infestations in dogs (12%) (24), especially in small puppies.…”
Section: Discussionmentioning
confidence: 61%
“…In a previous study of 50 clinically healthy subjects (32 men and 18 women), we found 6% (n = 3) seroprevalence for toxocariasis in ELISA and 4% (n = 2) in WB [31]. Comparison among the group of the patients with inflammatory heart disease and the group of clinically healthy blood donors showed relatively higher prevalence of specific anti-Toxocara antibodies in the first group (7.3% versus 6% in ELISA and 7.3% vs. 4% in WB), but the positive serology is not sufficient to provide a definitive diagnosis and the statistical comparison showed no significant difference (2X2 contingency table, Fisher's exact test, p=0.654).…”
Section: Discussionmentioning
confidence: 68%